Gênero digital: o Blog no contexto escolar: uma proposta pedagógica para a promoção do letramento digital - Santos, Margareth Maura dos (2018)
This study has the goal to investigate about the approach Digital Genre, especially, the Blog, in the Elementary school and High school. After, verifying some schoolbooks and reading some academic studies like thesis, as well talking to teachers of Portuguese, it came the interest to undertake this research in order to contribute for an inclusive education, that gives students and teachers the opportunity to insert the tecnologies and communications of this modernity in education. The methodology of reserarch was qualitative, one interviews and questionnaires were analyzed obtained through Google Docs, where the of teachers Portuguese the Brazilian States of Rio de Janeiro and Minas Gerais participated and they contributed for this study. Considering the new information and communication technologies, the students are connected and they have contact with a diversity of Digital Genres, this research investigated how the teachers treat the Digital Genres in the classrooms, in specific the Blog, and which are the perspectives of the teachers in working this Genre in real situations of language use practices. Moreover, pedagogical aspects that give the teacher training for promotion of Digital Literacy. The results pointed out that the teachers must improve the knowledge about the Digital Genres for them to demonstrate the strategies and to make the students to understand about the real finality of language on social. Therefore, it is possible to verify that introducing the Digital Genre Blog in the classes this makes possible for students to rase awareness of their language, and for them to manage organizing their discourses in a determinated context, and this way for them to develop many skills and abilities.